An Optimized FPGA Implementation of CAN 2.0 Protocol Error Detection Circuitry - Md Farukh Hashmi; Avinash G. Keskar (Institute of Advanced Engineering and Science, 2017)
Controller Area Network is an ideal serial bus design suitable for modern embedded system based networks. It finds its use in most of critical applications, where error detection and subsequent treatment on error is a critical issue. CRC (Cyclic Redundancy Check) block was developed on FPGA in order to meet the needs for simple, low power and low cost wireless communication. This paper gives a short overview of CRC block in the Digital transmitter based on the CAN 2.0 protocols. CRC is the most preferred method of encoding because it provides very efficient protection against commonly occurring burst errors, and is easily implemented. This technique is also sometimes applied to data storage devices, such as a disk drive. In this paper a technique to model the error detection circuitry of CAN 2.0 protocols on reconfigurable platform have been discussed? The software simulation results are presented in the form of timing diagram.FPGA implementation results shows that the circuitry requires very small amount of digital hardware. The Purpose of the research is to diversify the design methods by using VHDL code entry through Modelsim 5.5e simulator and Xilinx ISE8.3i.The VHDL code is used to characterize the CRC block behavior which is then simulated, synthesized and successfully implemented on Sparten3 FPGA .Here, Simulation and Synthesized results are also presented to verify the functionality of the CRC -16 Block. The data rate of CRC block is 250 kbps .Estimated power consumption and maximum operating frequency of the circuitry is also provided.